9 Box Talent Management di Pemerintah Kota Surabaya: Pendekatan strategis untuk pengembangan sumber daya manusia - Wahyuni, Ken; Suhariadi, Fendy; Subhekti, Erick Fajar (MBR (Management and Business Review), 2023)
This study is conducted with the aim of delving into the implementation of 9 Box Talent Management within the Surabaya City government. The research method used was a qualitative approach using purposive sampling technique to select 7 key informants. The research findings indicate that the implementation of 9 Box Talent Management in Surabaya City Government divides ASN into three main groups, namely Top Talent, Future Talent, and Development Focus. The contribution of this research lies in a deeper understanding of the science of human resource development through talent management practices, especially in public service organizations. The results of the study can assist organizations in determining potential leaders more accurately through the identification and grouping of appropriate talents.